2019
DOI: 10.1021/acsomega.8b03576
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Surface Deposits on Steel and Titanium Aviation Fuel Tubes under Real Operating Conditions

Abstract: In this study, stainless steel and titanium (Ti) tubes obtained from a turbofan engine after the end of its lifetime were analyzed in order to compare the amount of pyrolytic coke present and its influence on the parent, base material. Various analytical techniques including microhardness and topographical evaluations, optical emission spectrometry (OES), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS) were applied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
(88 reference statements)
1
2
0
Order By: Relevance
“…Using ALD to control the surface chemistry of substrates, we examine the role of surface chemistry in the Py autoxidation process. Our work confirms recent indications that surface processes are critical to pyrrolic autoxidation mechanisms and gum formation in fuels and reveals new insight into the origins of these effects. Using gas-phase QCM studies of Py adsorption and polymerization, we find that Lewis basic Py adsorbs to Lewis acid surface sites via exergonic hydrogen-bonding interactions of −1.5–2.8 kcal/mol.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using ALD to control the surface chemistry of substrates, we examine the role of surface chemistry in the Py autoxidation process. Our work confirms recent indications that surface processes are critical to pyrrolic autoxidation mechanisms and gum formation in fuels and reveals new insight into the origins of these effects. Using gas-phase QCM studies of Py adsorption and polymerization, we find that Lewis basic Py adsorbs to Lewis acid surface sites via exergonic hydrogen-bonding interactions of −1.5–2.8 kcal/mol.…”
Section: Discussionsupporting
confidence: 89%
“…For example, acidic conditions have been found to accelerate pyrrole (Py) autoxidation and depending on the specific fuel conditions, Py autoxidation has been found to proceed via different pathways, e.g., via peroxide intermediates or pyrrolines. However, despite these indicators that the homogeneous fuel environment influences the rate of autoxidation, studies comparing Py autoxidation rates in fuels of different origins do not reveal clear trends connecting fuel composition with the varying rates of polymer/gum formation or gum composition. , Another aspect through which the molecular environment is expected to influence the rate of autoxidation is through heterogeneous interactions with surfaces. Indeed, recent studies have found that the same fuel composition exhibits different rates of polymer gum formation when in contact with different surfaces. These studies suggest that surface chemistry may be a confounding variable in other studies and that understanding the role of heterogeneous surface processes on Py autoxidation may be crucial for developing strategies to mitigate autoxidation. We note that although Py is commonly alkylated in fuels, ,, we employ nonalkylated Py in this study to avoid confounding variables of steric hindrance and electron donating/withdrawing groups and direct our focus on fundamental mechanistic understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The authors were able to prove a direct relation between the size of aggregates, particle numbers, and changes in visual parameters when the cluster particle size was above 3500 g/mol. Scanning electron microscopy and energy-dispersive X-ray spectroscopy techniques were also successfully employed in analyzing a real stainless steel-titanium turbofan tube at the end of the lifetime by Velkavrh et al 141 They showed how the concentration of the metal elements from the pyrolytic coke followed an inverse trend with distance from the deposit surface, providing useful evidence about the dynamics of the deposit formation during real engine operations. The accuracy of these techniques, coupled with increased attention in the green-diesel production, can help gain an understanding of the whole oxidation process.…”
Section: Further Chemical Analytical Techniquesmentioning
confidence: 99%